Chemotherapy-induced miR-141/MAP4K4 signaling suppresses progression of colorectal cancer - Wang, Feifei (Biosci Rep, 2018)
One of the treatment failures for colorectal cancer (CRC) is resistance to chemotherapy drugs. miRNAs have been demonstrated to be a new regulator of pathobiological processes in various tumors. While few studies have explored the specific role of miR-141 in mediating 5-fluorouracil (5-FU) sensitivity of CRC cells, the present study aimed to detect the contribution of miR-141 in 5-FU sensitivity. The CRC cells viability was measured by MTS assay and cell colony forming. The expression of miR-141 and its downstream targets were assessed by reverse transcription quantitative PCR, Western blotting, and immunohistochemistry. The functional assays were conducted using CRC cells and nude mice. At the present study, we found overexpression of miR-141 could inhibit proliferation, migration, tumor-forming and invasive potential of CRC cells in vitro and mitogen-activated protein kinase kinase kinase kinase 4 (MAP4K4) was verified as a directed target of miR-141. The combination treatment of miR-141 with 5-FU, directly targetting MAP4K4, could better inhibit invasion and metastasis of CRC cells colony than either one alone. Furthermore, overexpression of miR-141, targetting MAP4K4, enhanced the effected of 5-FU and suppressed the malignant biological behaviors, in vivo. Our findings showed that 5-FU inhibited malignant behavior of human CRC cells in vitro and in vivo by enhancing the efficiency of miR-141. Our data suggested that targetting the miR-141/MAP4K4 signaling pathway could be a potential molecular target that may enhance chemotherapeutic efficacy in the treatment of CRC.